Skill Biased Technological Change and Endogenous Benefits: The Dynamics of Unemployment and Wage Inequality - Matthias Weiss; Alfred Garloff (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
In this paper, we study the effect of skill-biased technological change on unemployment when benefits are linked to the evolution of average income and when this is not the case. In the former case, an increase in the productivity of skilled workers and hence their wage leads to an increase in average income and hence in benefits. The increased fallback income, in turn, makes unskilled workers ask for higher wages. As higher wages are not justified by respective productivity increases, unemployment rises. More generally, we show that skill-biased technological change leads to increasing unemployment of the unskilled when benefits are endogenous. The model provides a theoretical explanation for diverging developments in wage inequality and unemployment under different social benefits regimes: Analyzing the social legislation in 14 countries, we find that benefits are linked to the evolution of average income in Continental Europe but not in the U.S. and the UK. Given this institutional difference, our model predicts that skill-biased technological change leads to rising unemployment in Continental Europe and rising wage inequality in the U.S. and the UK.
Keywords: O30; E24; J50; J31; 330; Unemployment; Skill-Biased Technological Change; Benefits; Arbeitslosigkeit; Lohnstruktur; Technischer Fortschritt; Qualifikation; Mehr-Sektoren-Modell; Faktorsubstitution; Relativer Preis; Theorie